1991
DOI: 10.2337/diab.40.6.673
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of In Vivo β-Cell Function Tests With β-Cell Mass and Pancreatic Insulin Content in Streptozocin-Administered Baboons

Abstract: In vivo beta-cell function tests are used increasingly in humans during the preclinical phase of insulin-dependent diabetes mellitus (IDDM), but the severity of the beta-cell loss responsible for the abnormalities seen in these tests is unknown. We have measured several physiological beta-cell function tests--fasting plasma glucose, glucose disappearance constant, fasting insulin, acute insulin responses to arginine (AIRarginine) and glucose (AIRglucose), and glucose potentiation of AIRarginine (delta AIRargin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 42 publications
(71 reference statements)
2
45
4
Order By: Relevance
“…Alternatively, it is possible that either AIR or PI (or both) may reflect the overall health or volume of the pancreatic ␤-cell mass. It has been demonstrated that AIR glucose correlates strongly and significantly with directly measured ␤-cell mass and pancreatic insulin content (r ϭ 0.63, P Ͻ 0.02; r ϭ 0.92, P Ͻ 0.001; respectively) in baboons that had received varying doses of streptozocin (47). In addition, a reduced ␤-cell mass could conceivably result in elevated PI concentration, in that the rate of secretion by remaining cells is increased, thereby decreasing the intracellular stores and forcing the release of incompletely processed materials (43).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that either AIR or PI (or both) may reflect the overall health or volume of the pancreatic ␤-cell mass. It has been demonstrated that AIR glucose correlates strongly and significantly with directly measured ␤-cell mass and pancreatic insulin content (r ϭ 0.63, P Ͻ 0.02; r ϭ 0.92, P Ͻ 0.001; respectively) in baboons that had received varying doses of streptozocin (47). In addition, a reduced ␤-cell mass could conceivably result in elevated PI concentration, in that the rate of secretion by remaining cells is increased, thereby decreasing the intracellular stores and forcing the release of incompletely processed materials (43).…”
Section: Discussionmentioning
confidence: 99%
“…A question that arises from the present study is: what is the significance of an ϳ60% decrease in ␤-cell mass in humans? Although rodents tolerate a partial pancreatectomy in which up to 80% of the ␤-cell mass is removed (28), primates (29) and pigs (30) develop diabetes with a decrease of ␤-cell mass of ϳ50% or greater. Furthermore, humans who have had ϳ50% of their pancreas removed have abnormal glucose tolerance (some developing diabetes by more recent classification) and diminished insulin secretion in response to a hyperglycemic clamp (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are also consistent with the previous finding by other investigators [35] who observed that insulin-treated Type II diabetic subjects contained lower beta-cell volume (mean: 0.41 ml) than subjects treated with oral compounds (0.52 ml) and diet (0.8 ml). Massive loss of beta cells such as that observed in a 95 %-partial pancreatectomy in rodents [36] or a 50 % reduction of beta-cell mass in streptozotocin-injected baboons [37] is required to induce hyperglycaemia. It is not therefore likely that the reduction of beta-cell mass found in our study could, by itself, account for the onset of diabetes.…”
Section: Discussionmentioning
confidence: 99%